Water as a Fundamental Right: State Responsibilities and Regional Water Supply System Solutions - Muh. Ali Masnun; Noviyanti Noviyanti; Irwan Bagyo Santoso; Bayangsari Wedhatami; Adrianus Abiyoga (Universitas Negeri Surabaya, 2024)
Management of water resources in Indonesia must actually be based on constitutional provisions which seek to guarantee the fulfillment of the right to water for the community in realizing prosperity. This research aims at the position of PT AB East Java (Perseroda) being given authority and responsibility in managing Probolajang Regional SPAM, in accordance with applicable laws and regulations. This research is normative legal research with an analytical and statutory approach. The research results confirm that the management of water resources in Indonesia is constitutionally subject to the provisions of Article 33 of the 1945 Constitution of the Republic of Indonesia where the state has the authority to regulate, manage, implement policies, and supervise the management of water resources. This has implications for the management of water resources by Regional Companies (Perseroda) which must balance between a profit-based orientation and the provision of public services in the form of providing adequate and quality water resources for the community. PT AB East Java, which has the status of a Regional Company (Perseroda), is an entity owned by the Regional Government of East Java Province which is not only focused on public services but also on achieving profitability.